Application of QR Code In Improving Public Knowledge About Beyond Use Date (BUD) of Medicine In Tanjung Rejo Village Percut Sei Tuan Deli Serdang: Penerapan QR Code Dalam Peningkatan Pengetahuan Masyarakat Tentang Beyond Use Date (BUD) Obat di Desa Tanjung Rejo Percut Sei Tuan Deli Serdang - Rambe, Robiatun; Pangondian, Aswan; Sugito, Sugito; Sakira, Dila; Monalisa, Anggi (Universitas Haji Sumatera Utara, 2025)
Community behavior in the use and storage of drugs is a contributing factor to the emergence of unexpected events during therapy. The community needs to know the Beyond Use Date (BUD) information in order to use drugs correctly and ensure their safety. Current technological developments can be utilized to improve the quality of health services. One of the technological developments that can help in pharmaceutical services is the QR Code (Quick Response Code). This community service aims to implement a QR Code system to help PKK mothers improve community knowledge about the Beyond Use Date (BUD). This activity was carried out using the lecture method and providing QR Codes containing audiovisual education. The target of this activity was PKK mothers in Tanjung Rejo Village, Percut Sei Tuan, Deli Serdang. The instruments used included PowerPoint presentations, educational QR Codes, and questionnaires. The results of the pretest and posttest showed an increase in knowledge after the activity was carried out. The results obtained in the Pretest questionnaire were included in the category of poor knowledge (0-59%) with an average value of 47%. Meanwhile, the level of PKK knowledge about Beyond Use Date (BUD) in the Posttest questionnaire is included in the good knowledge category (75-100%) with an average value of 79%. For the development of QR Code in delivering information to patients, on average, patients answered yes, but some did not agree. The conclusion of this service is that there was an increase in the level of PKK knowledge about Beyond Use Date (BUD) after being given drug information delivery using QR Code containing audiovisual (Postest), when compared to knowledge before being given the drug information delivery (Pretest).